Histone Lysine Demethylases KDM5B and KDM5C Modulate Genome Activation and Stability in Porcine Embryos - Glanzner, Werner Giehl; Gutierrez, Karina; Rissi, Vitor Braga; de Macedo, Mariana Priotto; Lopez, Rosalba; Currin, Luke; Dicks, Naomi; Baldassarre, Hernan; Agellon, Luis B.; Bordignon, Vilceu (Frontiers in Cell and Developmental Biology, 2020)
The lysine demethylases KDM5B and KDM5C are highly, but transiently, expressed in porcine embryos around the genome activation stage. Attenuation of KDM5B and KDM5C mRNA hampered embryo development to the blastocyst stage in fertilized, parthenogenetically activated and nuclear transfer embryos. While KDM5B attenuation increased H3K4me2-3 levels on D3 embryos and H3K4me1-2-3 on D5 embryos, KDM5C attenuation increased H3K9me1-3 on D3 embryos, and H3K9me1 and H3K4me1 on D5 embryos. The relative mRNA abundance of EIF1AX and EIF2A on D3 embryos, and the proportion of D4 embryos presenting a fluorescent signal for uridine incorporation were severely reduced in both KDM5B- and KDM5C-attenuated compared to control embryos, which indicate a delay in the initiation of the embryo transcriptional activity. Moreover, KDM5B and KDM5C attenuation affected DNA damage response and increased DNA double-strand breaks (DSBs), and decreased development of UV-irradiated embryos. Findings from this study revealed that both KDM5B and KDM5C are important regulators of early development in porcine embryos as their attenuation altered H3K4 and K3K9 methylation patterns, perturbed embryo genome activation, and decreased DNA damage repair capacity.